2000
DOI: 10.1007/s005350070081
|View full text |Cite
|
Sign up to set email alerts
|

Multiple hepatic adenomas caused by long-term administration of androgenic steroids for aplastic anemia in association with familial adenomatous polyposis

Abstract: We report a rare case of hepatic adenomas (HA), in a 20-year-old Japanese girl treated for 6 years with anabolic androgens for aplastic anemia. In a review of the world literature using computer MEDLINE search, we found only 17 cases of androgen-induced HA published between 1975 and 1998 in the English-language literature. The patient was referred to us because of liver lesions detected during a follow-up examination for familial adenomatous polyposis. After being diagnosed with aplastic anemia at 14 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 23 publications
2
47
0
1
Order By: Relevance
“…Almost all hepatic adenomas arise in one of three clinical settings: (1) reproductive age women, usually with a history of oral contraceptive pill (OCP) therapy (1), (2) excess androgen exposure such as in patients on androgen steroid therapy for Fanconi's anemia (2,3), and (3) glycogen storage disease Types I and III (4). Rare cases of hepatic adenomas have also been reported in a number of other clinical settings.…”
mentioning
confidence: 99%
“…Almost all hepatic adenomas arise in one of three clinical settings: (1) reproductive age women, usually with a history of oral contraceptive pill (OCP) therapy (1), (2) excess androgen exposure such as in patients on androgen steroid therapy for Fanconi's anemia (2,3), and (3) glycogen storage disease Types I and III (4). Rare cases of hepatic adenomas have also been reported in a number of other clinical settings.…”
mentioning
confidence: 99%
“…According to our literature review, only seven cases, including our case, have been reported (Table 1) [5,[10][11][12][13][14] .…”
Section: Discussionmentioning
confidence: 96%
“…Gastroendoscopy also found thick polyps without carcinoma. On the basis of clinical features [15] and previous literature [10][11][12][13] , we performed a total colectomy and ileoanal anastomosis and hepatic posterior sectoriectomy on December 2008. Macroscopically, numerous polyps of various sizes, including one lateral spreading tumor in the ascending colon, were found in the mucosal surface of the resected colon specimen.…”
Section: Case Reportmentioning
confidence: 99%
“…Although most adenomas are solitary, in 20-30% of cases multiple adenomas can be found [2]. It is associated with the use of exogenous sex steroids including oral contraceptives and anabolic androgens [3,4]. One of the complications of hepatic adenoma is intraperitoneal hemorrhage from rupture.…”
Section: Discussionmentioning
confidence: 99%